Prevalence and Clinical Significance of Metabolic Syndrome in Fibromyalgia Patients - Yahia, Mohamed; Makboul, Khaled; Ali, Hany (Aktuelle Rheumatologie, 2021)
Background and Objective Fibromyalgia syndrome (FMS) is a distressing clinical condition. Metabolic syndrome (MetS) is a biochemical and clinical condition characterised by visceral obesity, dyslipidaemia, hyperglycaemia and hypertension. The relation between the two conditions is rarely discussed. This study aimed to determine the prevalence of MetS in FMS patients and to uncover its association with the clinical severity of FMS.Patients and Methods This cross-sectional study included 200 patients with newly diagnosed FMS. The diagnosis of FMS was established on the basis of the American College of Rheumatology (ACR) 2016 revised criteria. Patients were assessed using the validated Arabic version of Fibromyalgia Impact Questionnaire (FIQ). FMS severity was categorised according to FIQ scores into mild (≤45), moderate (>46 and≤65), and severe (>65).Results The study included 200 FMS patients. They comprised 180 females (90.0%) and 20 males (10.0%). Among the studied patients, there were 96 patients (48.0%) who fulfilled the criteria of MetS diagnosis. A comparison between FMS patients with MetS and patients without MetS revealed a significantly higher Widespread Pain Index (WPI) [median (IQR): 12.0 (10.0–17.0) vs. 9.0 (6.0–11.0), p<0.001], a higher Symptoms Severity Scale (SSS) (10.5±1.04 vs. 8.1±1.8, p<0.001) and a higher FIQ (58.8±20.7 vs. 45.4±16.6) in patients with MetS. Patients with MetS had a significantly higher frequency of severe FMS (31.2 vs. 10.6%, p<0.001). Using binary logistic regression analysis, significant predictors of severe FMS included WPI, SSS and MetS in a univariate analysis. However, in a multivariate analysis, only WPI and SSS remained significant.ConclusionsThis study found that MetS is prevalent in FMS patients and it may be associated with more severe forms of the disease.
Keywords: psychosomatic pain; fibromyalgia; metabolic syndrome; chronic pain; Widespread Pain Index